Implementasi Modul Mnemonic “Sambas” dengan Sebagai Media Pembelajaran Pertolongan Pertama Kasus Trauma di SMKN 1 Sukadana Kayong Utara: Penelitian - Debby Hatmalyakin; Uti Rusdian Hidayat; Ali Akbar; Nurpratiwi; Fauzan Alfikrie; Defa Arisandi; Mimi Amaludin; Nur Annisa; Ihsan Angga Anjarwadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Trauma cases often occur not only in densely populated areas but also in regions with tourist destinations. In developing tourist areas, developers are not only required to prepare tourist facilities, but their human resources must also be equipped with skills in providing initial treatment for injuries or trauma. The method used for community service was a simulation of first aid for trauma cases using the SAMBAS Mnemonic module. The results of community service obtained data showing an increase in community skills before and after the simulation on first aid for trauma cases using the SAMBAS Mnemonic module. These results indicate that learning with SAMBAS Mnemonics can improve knowledge and skills. Improving skills in first aid for trauma cases is an effort to handle emergency conditions related to trauma cases.